EFFICACY OF STANDALONE ORAL METHYLCOBALAMIN IN THE MANAGEMENT OF DIABETIC DISTAL SYMMETRIC POLYNEUROPATHY IN INDIA: A SYSTEMATIC REVIEW - Dr Himadri Pathak, Dr Mukuta Medhi, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background: Diabetic distal sensory Polyneuropathy (DSPN) is an annoying and disablingcomplication of long standing type 2 diabetes mellitus (T2DM). These patients are also deficient invitamin B12. Methylcobalamin (MeCbl), an active form of vitamin B12, is widely used in Indiaespecially by prim